Integrating Triple-Helix System in Agricultural Education Programme for Development of Employability Skills Among Students in Rivers State - Aleru P.D; Obele I.T (International Journal of Integrative Sciences, 2023)
The study examined how the integration of triple-helix system in agricultural education programme would develop students’ employability skills in Rivers State. The study adopted a descriptive survey with three research questions. A random sampling technique was used to select 122 (106 students and 16 lecturers) respondents in agricultural education from the population of 350 in Rivers State University and Ignatius Ajuru University of Education. A self-structured questionnaire designed in 4-point rating scale of agreement was used for gathering data. Data was analyzed using mean and standard deviation with a benchmark mean of ≥ 2.50. Findings from the study revealed that the integration of triple-helix system in agricultural education programme would develop students’ managerial skills such as enhancing their knowledge in planning, communication and risk management skill among others. Finally, it was also found that students would develop fresh ideas towards solving agricultural problems, imaginative thinking for production of agricultural value-addition, critical thinking skills for decision making, initiative skill for alternative method of food processing and skills for improved packaging of agricultural products when triple-helix system is incorporated into vocational agricultural education programme